GUARANTEES FOR THE PROTECTION OF JOURNALISTIC SOURCES IN THE APPLICATION OF TEMPORARY ACCESS TO THINGS AND DOCUMENTS - Лисаченко, Є. І.; Денисенко , Г. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2021)
Abstract. The article is devoted to the study of guarantees of protection of journalistic sources when applying temporary access to things and documents in the criminal procedural law of Ukraine. Based on the analysis of the current criminal procedural legislation of Ukraine, the author defines the subject matter of journalistic secrecy, which is: 1) a source of information; 2) information which is held/received by a journalist or a media outlet with a view to its dissemination or use in their professional activities; 3) any other information (documents, records) which allow establishing a connection between a journalist and a source of information. The author establishes that the lack of proper judicial control over the legality of investigators’ claims, the formal approach to consideration of applications for temporary access to things and documents, and the impossibility of appealing against the relevant rulings on appeal create a risk of disclosure of information in the possession of a media outlet or a journalist and provided to them on condition that the authorship or source of information is not disclosed. It is proved that the use of temporary access to things and documents containing legally protected information, in particular, information in the possession of a media outlet or a journalist and provided to them on condition that the authorship or source of information is not disclosed, without a ruling of an investigating judge or a court is inadmissible. The European Court of Human Rights has determined in a number of decisions that disclosure of sources is acceptable only in exceptional cases when it comes to protecting vital interests. These include cases of sexual abuse of children, disclosure of particularly serious crimes, etc. However, the decision to disclose the source of information must be made by an independent and impartial judicial authority and must contain a detailed justification why the disclosure of journalistic «sources» of information outweighs the journalist’s right to keep them secret. It is important to emphasize the need to eliminate formalism in the consideration of motions for temporary access to things and documents, and especially in cases involving information containing legally protected secrets (in particular, the secrecy of journalistic sources). In such cases, the law requires that the investigating judge find a fair balance between the right to secure criminal proceedings for the purpose of to solve the crime and the right to keep secrets protected by law, in particular the secrecy of journalistic sources (see para. 1, part 1, Article 162, part 6, Article 163 of the CPC of Ukraine). In view of this, the practice of considering such motions within 5–5 minutes should be recognized as unacceptable. motions within 4–5 minutes, as this does not allow for a thorough familiarization with the case file, conduct an appropriate analysis, and make a reasoned decision.

Анотація. Стаття присвячена вивченню гарантій захисту журналістських джерел при застосуванні тимчасового доступу до речей і документів у кримінальному процесуальному праві України. На підставі аналізу чинного кримінального процесуального законодавства України в роботі визначено предмет журналістської таємниці, яким виступає: 1) джерело інформації; 2) інформація, яка знаходиться/отримана журналістом або засобом масової інформації з метою її поширення чи використання у своїй професійній діяльності; 3) будь-які інші відомості (документи, записи), які дозволяють встановити зв’язок між журналістом та джерелом інформації. Встановлено, що відсутність належного судового контролю за законністю вимог слідчих, формальний підхід до розгляду клопотань про тимчасовий доступ до речей і документів, а також неможливість оскарження відповідних ухвал в апеляційному порядку створюють небезпеку розголошення інформації, що знаходиться у володінні засобу масової інформації або журналіста і надана їм за умови нерозголошення авторства або джерела інформації. Доведено, що застосування тимчасового доступу до речей і документів, що містять охоронювану законом інформацію, зокрема таку, що знаходиться у володінні засобу масової інформації або журналіста і надана їм за умови нерозголошення авторства або джерела інформації, без ухвали слідчого судді, суду є неприпустимим.
ГАРАНТІЇ ЗАХИСТУ ЖУРНАЛІСТСЬКИХ ДЖЕРЕЛ ПРИ ЗАСТОСУВАННІ ТИМЧАСОВОГО ДОСТУПУ ДО РЕЧЕЙ І ДОКУМЕНТІВ
Keywords: criminal proceedings; evidence; temporary access to things and documents; legally protected secrets; journalistic sources; кримінальне судочинство; доказування; тимчасовий доступ до речей і документів; охоронювана законом таємниця; журналістські джерела